Adverse Event Detection and Labeling in Pediatric Drug Development: Antiretroviral Drugs. (March 2015) - Momper, Jeremiah D.; Chang, Yang; Jackson, Matthew; Schuette, Paul; Seo, Shirley; Younis, Islam; Abernethy, Darrell R.; Yao, Lynne; Capparelli, Edmund V.; Burckart, Gilbert J.
Background: Pediatric safety studies are conducted for drugs undergoing development for use in pediatric patients. The objective of this study was to describe safety studies and compare adverse events of antiretroviral drugs between pediatric patients and adult subjects. Methods: Pediatric and adult adverse event data were obtained from US Food and Drug Administration (FDA)–approved drug labels for 9 antiretroviral drugs with pediatric indications approved by the FDA prior to 2013. For adverse events (AEs) reported in both pediatric patients and adult subjects, the risk difference (RD) and associated confidence interval (CI) were calculated. Results: Of 35 drug-AE combinations, 10 AEs were reported at statistically significantly ( P < .05) higher incidence rates in the pediatric population than in the adult population, and 3 AEs were reported at statistically significantly higher rates in the adult population than in the pediatric population. The largest differences where the risk of an AE was greater in pediatric patients than in adult subjects were for rash with efavirenz (RD = 36.24% [95% CI, 21.1 to 50.53]), diarrhea with efavirenz (RD = 24.53% [95% CI, 9.06 to 39.57]), and rash with nevirapine (RD = 16.14% [95% CI, 9.7 to 24.27]). The largest differences where the risk of an adverse event was lower in pediatric patients than in adult subjects were for headache with abacavir (RD = –12% [95% CI, –16.81 to –6.89]), diarrhea with tipranavir (RD = –11.32% [95% CI, –15.02 to –5.6]), and diarrhea with lamivudine (RD = –9.88% [95% CI, –15.91 to –3.98]). Conclusions: The adult adverse event experience provides preliminary data for pediatric drug safety, yet the specific types of adverse effects and frequencies may not be predicted in children based exclusively on adults. As adult safety data do not fully inform the pediatric safety profile, pediatric safety studies should continue to be conducted separately for drugs undergoing testing in pediatric patients.